Colonization and infection due to carbapenemase-producing Enterobacteriaceae in liver and lung transplant recipients and donor-derived transmission: a prospective cohort study conducted in Italy. (February 2019) - Errico, G.; Gagliotti, C.; Monaco, M.; Masiero, L.; Gaibani, P.; Ambretti, S.; Landini, M.P.; D'Arezzo, S.; Di Caro, A.; Parisi, S.G.; Palù, G.; Vespasiano, F.; et al.
Abstract: Objectives: A prospective cohort study was conducted in Italy in order to describe the microbiologic aspects of colonization/infection by carbapenemase-producing Enterobacteriaceae (CPE) in donors and recipients of lung and liver transplants and the possible CPE transmission from donors to recipients. Methods: Between 15 January 2014 and 14 January 2015, all recipients of solid organ transplants (SOT) at ten lung and eight liver transplantation centres and the corresponding donors were enrolled. Screening cultures to detect CPE were performed in donors, and screening and clinical cultures in recipients with a 28-day microbiologic follow-up after receipt of SOT. Detection of carbapenemase genes by PCR, genotyping by multilocus sequence typing, and pulsed-field gel electrophoresis and whole-genome sequencing were performed. Results: Of 588 screened donors, 3.4% were colonized with CPE. Of the liver first transplant recipients ( n = 521), 2.5% were colonized before receipt of SOT and 5% acquired CPE during follow-up. CPE colonization was higher in lung first transplant recipients ( n = 111, 2.7% before SOT and 14.4% after SOT). CPE infections occurred in 1.9% and 5.3% of liver or lung recipients, respectively. CPE isolates were mostly Klebsiella pneumoniae carbapenemase (KPC)-producing K. pneumoniae belonging to CG258. Three events of donor–recipient CPE transmission, confirmed by whole-genome sequencing and/or pulsed-field gel electrophoresis, occurred in lung recipients: two involving K. pneumoniae sequence type 512 and one Verona integron-encoded metallo-β-lactamase (VIM)-producing Enterobacter aerogenes. Conclusions: This study showed a low risk of donor–recipient CPE transmission, indicating that donor CPE colonization does not necessarily represent a contraindication for donation unless colonization regards the organ to be transplanted. Donor and recipient screening remains essential to prevent CPE transmission and cross-infection in transplantation centres.